2016
DOI: 10.5114/fn.2016.62233
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid-mediated sonosensitization of rat RG2 glioma cells in vitro

Abstract: A b s t r a c t Sonodynamic therapy (SDT) is a promising technique based on the ability of certain substances

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…First preclinical studies [ 57 , 58 ] regarding 5-ALA SDT safety demonstrated that no harm was exerted to surrounding healthy brain tissue using a peak power of 10 W/cm 2 on a deep-seated glioma model; moreover, the treatment protocol highlighted a much greater reduction in tumor volume in the SDT group compared to controls. Bilmin et al [ 60 ] reported that 5-ALA SDT caused marked cytotoxic effects in a rat RG2 glioma cell line, leading to decreased tumor cell viability, chromatin condensation and presence of apoptosis.…”
Section: Sonosensitizers For Brain Tumorsmentioning
confidence: 99%
“…First preclinical studies [ 57 , 58 ] regarding 5-ALA SDT safety demonstrated that no harm was exerted to surrounding healthy brain tissue using a peak power of 10 W/cm 2 on a deep-seated glioma model; moreover, the treatment protocol highlighted a much greater reduction in tumor volume in the SDT group compared to controls. Bilmin et al [ 60 ] reported that 5-ALA SDT caused marked cytotoxic effects in a rat RG2 glioma cell line, leading to decreased tumor cell viability, chromatin condensation and presence of apoptosis.…”
Section: Sonosensitizers For Brain Tumorsmentioning
confidence: 99%
“…In our previous study, we also observed a sonodynamic effect using 5-ALA in the rat glioma RG2 cell line. The biggest cytotoxic effect was observed for the combination 5-ALA and 6 W ultrasound power [49].…”
Section: Ala and Porphyrins In Pre-clinical Models Of Glioma: Resementioning
confidence: 99%
“…However, overproduction of ROS is more reactive than non-free radicals and easily reacts with other molecules, resulting in cell membrane lipid peroxidation, protein and DNA damage [20]. Previous studies have reported that the mechanism of SDT in cancer cells apoptosis was thought to be induced by acoustic cavitation [12,21]. Sonosensitizers are highly sensitive and selective to metabolically active cells.…”
Section: Histological Analysismentioning
confidence: 99%
“…Sonodynamic therapy (SDT) is a promising treatment for killing cancer cells using low-intensity ultrasound with sonosensitizers. When the low-intensity ultrasound reaches the target, it can activate sonosensitizers and generate reactive oxygen species (ROS) [12]. Hematoporphyrin monomethyl ether (HMME) is an effective sonosensitizer in SDT with a stable structure, lower dark toxicity, higher singlet oxygen yield to induce cell apoptosis via the mitochondrial apoptotic pathway [13].…”
Section: Introductionmentioning
confidence: 99%